2013
DOI: 10.1136/eb-2012-101216
|View full text |Cite
|
Sign up to set email alerts
|

Citations of scientific results and conflicts of interest: the case of mammography screening

Abstract: IntroductionIn 2001, a Cochrane review of mammography screening questioned whether screening reduces breast cancer mortality, and a more comprehensive review in Lancet, also in 2001, reported considerable overdiagnosis and overtreatment. This led to a heated debate and a recent review of the evidence by UK experts intended to be independent.ObjectiveTo explore if general medical and specialty journals differed in accepting the results and methods of three Cochrane reviews on mammography screening.MethodsWe ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
(32 reference statements)
0
17
0
3
Order By: Relevance
“…They evaluated the extent to which three Cochrane reviews on mammography screening that reported considerable overdiagnosis were cited by a general medical and specialty journals. The results for overdiagnosis were accepted by general medical journals in 11% (7 of 63) of articles in contrast to only 3% (3 of 108) (P = .05) ( Table 1) (35). They concluded that several specialty journals are published by interest groups and some authors have vested interests in mammography screening.…”
Section: Estimates Of Low Overdiagnosis Rate a Panel Of Experts Frommentioning
confidence: 96%
“…They evaluated the extent to which three Cochrane reviews on mammography screening that reported considerable overdiagnosis were cited by a general medical and specialty journals. The results for overdiagnosis were accepted by general medical journals in 11% (7 of 63) of articles in contrast to only 3% (3 of 108) (P = .05) ( Table 1) (35). They concluded that several specialty journals are published by interest groups and some authors have vested interests in mammography screening.…”
Section: Estimates Of Low Overdiagnosis Rate a Panel Of Experts Frommentioning
confidence: 96%
“…This is a common occurrence in specialist medical journals rather than in general practitioner journals. The former lower reporting rates of potential harms attributed to preventive initiatives, reflecting possibly a conflict of interest 42 . This makes it difficult to compare group D with groups A + C with regards to the harm/benefits net balance, exposing asymptomatic people to unnecessary harm.…”
Section: Technical and Ethical Considerationsmentioning
confidence: 99%
“…Esses últimos são mais explícitos em rejeitar dados de revisões sistemáticas e apresentam, com maior frequência, problemas de conflitos de interesses 55 .…”
Section: Entendendo O Sobrediagnósticounclassified